Man and creativity: a contrastive analysis between western and Islamic psychologies = Psychologies manusia dan kreativiti: analisis kontrastif di antara psikologi Barat dan Islam - Abdul Razak, Mohd Abbas; Afridi, Muhammad Adil Khan (IIUM Press, International Islamic University Malaysia, 2017)
Among all creations of God living in this planet, man is the most intelligent, innovative and creative. Imbued with these qualities, man was able to plan, create and recreate new things using the resources available in the environment. Man’s position as God’s best creation and as the recipient of the creative intelligence from his Creator has further advanced him in mastering science and technology. As a result of his advancement in knowledge and science in one way or another has ushered man into creating great civilizations. While the discussion goes on as to whether man’s creativity is an inborn or a learned behaviour, this paper intends to explore and analyze some of the existing concepts on human creativity found in Western and Islamic psychologies. Very particularly, the researchers would like to examine the concept of creativity put forward by Freudian Psychoanalysis, Behaviorists, Humanistic and Islamic psychologies. It is expected that the findings of this research can motivate mankind to be more dynamic and productive in bringing upon the much needed positive change to present world conditions.